PERKEMBANGAN SENI ANAK USIA DINI (STPPA TIDAK TERCAPAI): Studi Penelitian di RA Baiturrohmah, Tridadi, Sleman - Ade Saputro, Fery (El-Hamra, 2018)
Art is very important and has a big influence on the process of developing early childhood in various aspects. Early childhood will easily accept a fun learning process, because th world of early childhood is playing with learning, and art dominates the role of learning in early childhood. Starting from singing, dancing, drawing / painting, and so on. This study discusses the development of early childhood art that STTPA has not achieved. This research is descriptive qualitative research, data obtained from observation and interviews. The results of this study are (1) lack of achievement of the development of subject art (2) Subjects do not like art.Key Words: Art Development, early childhood